Evapoporometry : a novel technique for determining the pore-size distribution of membranes - Krantz, William B. (2013)
Synthetic membranes are used in applications such as controlled drug release, artificial organs, smart sensors, and water treatment that require knowing the pore-size distribution (PSD). Current PSD characterization methods can require dedicated and/or expensive equipment as well as special expertise to implement. Evapoporometry (EP) is a novel characterization technique based on vapor pressure depression that can accurately determine the pore size for ultrafiltration membranes using a simple diffusion cell and a microbalance. A straightforward characterization procedure and comprehensive error analysis are described. EP characterization of the PSD of a 100 nm bilayer Anopore™ membrane used as a standard is shown to compare favorably with the nominal pore diameter, FESEM analysis, and analyses reported by prior investigators. In addition, EP is utilized for PSD characterization of commercially fabricated 20 and 50 nm polyvinylidene fluoride (PVDF) membranes for which the results are compared with those obtained via liquid displacement porometry (LDP). The mean pore diameters determined by EP and LDP are in good agreement for the 50 nm PVDF membranes, but the lower values obtained via LDP for the 20 nm PVDF membranes may reflect the effects of high pressures that are not required in EP. The advantages and limitations of EP as well as other potential applications of this technique are discussed.